METHODS AND METHODS FOR THE DEVELOPMENT OF SPEECH OF PRESCHOOL CHILDREN - Rimbayeva Ozoda Bazarbayevna (Western European Studies, 2024)
the preschool age period is the main period in the development of our speech. This article will provide information about the methods and methods used in the development of speech of preschool children
Keywords: method; nut; education; phonemic perception